Northern News - North America, Arctic Institute of (ARCTIC, 1955)
The items include: 1) a brief history of the Danish Arctic Station at Godhavn, which is the oldest permanent biological laboratory in the Arctic, and information on how to apply to use the station by M. Westergaard; 2) details on the design and construction of a new Danish Arctic ship, the M.V. Magga Dan; 3) William S. Laughlin's report on a study by C.S. Chard concerning the Kamchadal culture and its relationship to the Asiatic and New World populations; and 4) a list of the main speakers and the titles of their talks that will be presented at the Symposium on Arctic and Alpine Tundras in East Lansing, Michigan.